2012
DOI: 10.1111/j.1538-7836.2012.04650.x
|View full text |Cite
|
Sign up to set email alerts
|

Circulating microparticles and endothelial progenitor cells in atherosclerosis: pharmacological effects of irbesartan

Abstract: Circulating microparticles and endothelial progenitor cells in atherosclerosis: pharmacological effects of irbesartan. J Thromb Haemost 2012; 10: 680-91.Summary. Aims: This study aimed to (i) employ our newly designed model, the hypertensive-hypercholesterolemic hamster (HH), in order to find out whether a correlation exists between circulating microparticles (MPs), endothelial progenitor cells (EPCs) and their contribution to vascular dysfunction and (ii) to assess the effect of irbesartan treatment on HH ani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
74
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(78 citation statements)
references
References 29 publications
4
74
0
Order By: Relevance
“…Literatures have reported that P-selectin is closely related to lipid metabolism disorders and atherosclerosis [31,32]. This study found that the inhibition of P-selectin expression by magnoline was associated with decreased blood lipids.…”
Section: Discussionmentioning
confidence: 63%
“…Literatures have reported that P-selectin is closely related to lipid metabolism disorders and atherosclerosis [31,32]. This study found that the inhibition of P-selectin expression by magnoline was associated with decreased blood lipids.…”
Section: Discussionmentioning
confidence: 63%
“…On the other hand, hypercholesterolemia was associated with vasa vasorum neovascularization, which is considered to be important in the progression of atherosclerotic disease. In another study in an animal model of atherosclerosis, Georgescu et al [38] showed that hypertension associated with hypercholesterolemia induced considerable changes consisting of lipid, collagen, and macrophage accumulation, activation of endothelial and smooth muscle cells, and synthesis of hyperplasic-multilayered basal lamina in the thoracic aortic arch and arteriole regions. Moreover, a considerably altered reactivity of the arterial wall was observed to be closely correlated with microparticles and endothelial progenitor cells adherence.…”
Section: The Effect Of Arterial Hypertension and Hypercholesterolemiamentioning
confidence: 99%
“…Clinical studies documented a decreased number of circulating EPCs in coronary artery disease (CAD) patients, suggesting that levels of circulating EPCs might be associated with vascular endothelial function and cardiovascular risk factors [17][18][19][20][21] . Hill et al [10] measured colony-forming units of EPCs from patients with different degrees of cardiovascular risk but without history of cardiovascular disease.…”
Section: Epc Number and Function In Cardiovascular Diseasesmentioning
confidence: 99%
“…It was also found that EPCs from subjects at high risk for cardiovascular events had higher rates of in vitro senescence than cells from subjects at low risk. Subsequently, it was demonstrated that reduced level of circulating EPCs independently predicts atherosclerotic disease progression and development of cardiovascular events [17][18][19] . Sen et al [17] , suggested that EPC determines the quality of the coronary collateral circulation.…”
Section: Epc Number and Function In Cardiovascular Diseasesmentioning
confidence: 99%
See 1 more Smart Citation